New Metal Complexes Derived from Mannich-Base Ligand; Synthesis, Spectral Characterisation and Biological Activity - Safaudeen A. Hussain (Journal of Global Pharma Technology, 2019)
In this work, the preparation of a new bidentate Mannich-base ligand and its metal complexes are reported. The formation of the ligand (R)-2-((R)-(4-(dimethylamino) phenyl)-(phenyl-amino) methyl) cyclohexan-1-one (HL) was achieved from the reaction of dimethylaminobenzaldehyde, aniline and cyclohexanone in a 3:3:5 mole ratio, respectively. The reaction of the ligand with Mn(II), Co(II), Ni(II), Cu(II), Zn(II) and Cd(II) metal ions in a 2:1 (L:M) mole ratio resulted in the isolation of monomeric complexes. The ligand and its metal complexes were characterised using a range of analytical and spectroscopic techniques including; elemental microanalysis, magnetic susceptibility, conductance FT-IR, electronic spectra, electrospray mass spectroscopy and 1H, 13C-NMR spectra. The characterisation data indicated the isolation of six and four coordinate monomeric complexes with the general formula; [M(HL1)2(Cl)2].(H2O)2 (where M= Mn(II), Co(II), Ni(II), Cu(II)) and [M(HL1)]Cl2.(H2O)2 (where M= Zn(II) and Cd(II)). The ligand and its complexes were screened against several bacterial strains and fungi species. The obtained data indicated that the complexes are more active against several kind of organism, under survey, compared with the free ligand.Keywords: Mannich-base ligand; Monomeric metal complexes; Structural study; Biological activity.